Targeted Next-Generation Sequencing Reveals Heterogenous Genomic Features in Viscerally Metastatic Prostate Cancer. Issue 2 (29th August 2021) - Gong, Yiming; Fan, Liancheng; Fei, Xiaochen; Zhu, Yinjie; Du, Xinxing; He, Yuman; Pan, Jiahua; Dong, Baijun; Xue, Wei
Abstract : Purpose: We sought to explore the genomic features of bone-only metastasis, hepatic metastasis and pulmonary metastasis without liver involvement in prostate cancer using targeted next-generation sequencing. Materials and Methods: A hybridization capture-based next-generation sequencing was performed to detected genomic alterations in 50 genes, including androgen receptor, DNA damage response and other clinical relevant drivers. Results: We successfully sequenced circulating tumor DNA from 109 blood samples and 29 metastatic tissue samples from 129 patients with metastatic castration-resistant prostate cancer (metastatic castration-resistant prostate cancer). We observed distinct genomic profiles of metastatic castration-resistant prostate cancer across various metastatic sites. High prevalence of PTEN alteration was found in viscerally metastatic prostate cancer compared with bone-only metastatic prostate cancer ( PTEN, 9.09% vs 2.08%, p=0.105). When comparing viscerally metastatic prostate cancer according to the metastatic sites, AR alteration rarely occurs in hepatically metastatic prostate cancer, which stood in great contrast to the high alteration frequency in hepatically metastatic prostate cancer (0.0% vs 42.1%, p=0.01). For overall DNA damage response alteration, the highest frequency was found in hepatically metastatic prostate cancer (63.2%). Conclusions: Through genomic profiling of prostate cancer across various metastatic sites, we identified an extremely low frequency of AR alterations in pulmonarily metastatic prostate cancer without liver involvement, high prevalence of DNA damage response pathway deficiency in hepatically metastatic prostate cancer and high PTEN alteration rates in viscerally metastatic prostate cancer. We discovered the genomic diversity among bone-only metastatic prostate cancer, hepatically metastatic prostate cancer and pulmonarily metastatic prostate cancer without liver involvement. Our findings shed new light on the heterogenous prognosis in visceral metastases and hint at potential therapeutic targets in both hepatically metastatic prostate cancer and pulmonarily metastatic prostate cancer without liver involvement.